A hydrogeological model of the open-cast mine Tamnava-West Field (Kolubara Coal Basin, Serbia) - Ratković Jelena; Polomčić Dušan; Bajić Dragoljub; Hajdin Bojan (Podzemni Radovi, 2016)
The Kolubara Coal Basin is the largest coal-producing area in Serbia. It is administratively comprised of several open-cast mines: Field A, Field B, Field C, Field D, Field E, Field F, Field G, Veliki Crljeni, Šopić-Lazarevac, Tamnava - West Field, Tamnava - East Field, Radljevo, Zvizdar, Ruklade, and Trlić. The paper focuses on the largest active open-cast mine: Tamnava - West Field. A study and conclusions about the hydrogeologic functions of the lithologic strata, and insight into their spatial interactions, are extremely important for hydrogeologic modeling of a given area. The main purpose of a hydrogeologic model is to derive conclusions about the spread of the aquifers in the study area, their interactions, and groundwater flow conditions. Based on geologic and hydrogeologic exploration, and analysis and synthesis of the collected data, the paper describes hydrogeologic modeling of the open-cast mine Tamnava - West Field. The software used in the research provides a portrayal of the 3D distribution of the aquifers present in the study area. As such, the hydrogeologic model constitutes a basis for developing a hydrodynamic (mathematical) model of the groundwater regime.